Tabling with Support for Relational Features in a Deductive Database - Sáenz-Pérez, Fernando (Electronic Communications of the EASST, 2013)
Tabling has been acknowledged as a useful technique in the logic programming arena for enhancing both performance and declarative properties of programs. As well, deductive database implementations benefit from this technique for implementing query solving engines. In this paper, we show how unusual operations in deductive systems can be integrated with tabling. Such operations come from relational database systems in the form of null-related (outer) joins, duplicate support and duplicate elimination. The proposal has been implemented as a proof of concept rather than an efficient system in the Datalog Educational System (DES) using Prolog as a development language and its dynamic database.